Odpowiedzi

2010-02-21T14:06:53+01:00
A) 3b+(b+1) = 3b+b+1 = 4b+1
b) 5a-(a+1) = 5a-a-1 = 4a-1
c)2x-(3-5-x) = 2x-3+5+x = 3x+2
d)2a+(3a-2b)+(a+b) = 2a+3a-2b+a+b= 6a-b
e)5a-(2-x)+b-2x+5 = 5a+2+x+b-2x+5=5a+b-x+7
f)7k-(m-2n+k)-(5k-3)+(2k-1) = 7k-m+2b-k-5k+3+2k-1 = 3k-m+2b+2
g)0,3x-(5+0,7y)-(0,9-0,1x)+(x-0,1) = 0,3x-5-0,7y-0,9+0,1x+x-0,1=1,4x-0,7y-6
h)0,5a+(5-0,8b+2a)-(-b+1) = 0,5a+5-0,8b+2a-b-1 = 2,5a-1,8b+4
i)¾-(¼x+½) = ¾-¼x-½ = ¼x+¾-2/4 = ¼x+¼
24 4 24
2010-02-21T14:12:42+01:00
A) 3b+b+1= 4b+1
b)5a-(a+1)= 5a-a-1=4a-1
c)2x-(3-5-x)= 2x-3+5+x = 3x+2
d)2a+(3a-2b)+(a+b)= 2a+3a-2b+a+b=6a+3b
e)5a-(2-x)+b-2x-5=5a-2+x+b-2x-5= 5a-7-x+b
f)7k-(m-2n+k)-(5k-3)+(2k-1)=7k-m+2n-k-5k+3+2k-1=8k-+2n+2
g)0,3x-(5+0,7y)-(0,9-0,1x)+(x-0,1)=0,3x-5-0,7y-0,9+0,1x+x-0,1=1,4x-4-0,7y
h)0,5a+(5-0,8b+2a)-(-b+1)=0,5a+5-0,8b+2a+b-1=2,5a+0,2b+4
i)¾-(¼x+½) =3/4- 1/4x-2/4= 1/4-1/4x
13 4 13
2010-02-21T14:18:23+01:00
A) 3b+(b+1) = 3b+b+1 = 4b+1
b) 5a-(a+1) = 5a-a-1 = 4a-1
c) 2x-(3-5-x) = 2x-3+5+x = 3x+2
d) 2a+(3a-2b)+(a+b) = 2a+3a-2b+a+b = 6a-b
e) 5a-(2-x)+b-2x+5 = 5a-2+x+b-2x+5 = 5a-x+b+3
f) 7k-(m-2n+k)-(5k-3)+(2k-1) = 7k-m+2n-k-5k+3+2k-1 = 3k-m+2n+2
g) 0,3x-(5+0,7y)-(0,9-0,1x)+(x-0,1) = 0,3x-5-0,7y-0,9+0,1x+x-0,1 = 0,4x-0,7y-6
h) 0,5a+(5-0,8b+2a)-(-b+1) = 0,5a+5-0,8b+2a+b-1 = 2,5a+0,2b+4
i) ¾-(¼x+½) = ¾-¼x-½ = -¼x+¼
11 4 11